CANDIDA ALBICANS VERSUS CANDIDA DUBLINIENSIS: WHY IS C. ALBICANS MORE PATHOGENIC? - COLEMAN, DAVID; SULLIVAN, DEREK; MORAN, GARY (My University, 2012)
Candida albicans and Candida dubliniensis are highly related pathogenic yeast species. However, C. albicans is far more prevalent in human infection and has been shown to be more pathogenic in a wide range of infection models. Comparison of the genomes of the two species has revealed that they are very similar although there are some significant differences, largely due to the expansion of virulence-related gene families (e.g., ALS and SAP) in C. albicans, and increased levels of pseudogenisation in C. dubliniensis. Comparative global gene expression analyses have also been used to investigate differences in the ability of the two species to tolerate environmental stress and to produce hyphae, two traits that are likely to play a role in the lower virulence of C. dubliniensis. Taken together, these data suggest that C. dubliniensis is in the process of undergoing reductive evolution and may have become adapted for growth in a specialized anatomic niche.
PUBLISHED
4th Septemebr; Epub ahead of print
Keywords: Dental Science; Candida dubliniensis; Genes & Society; Immunology, Inflammation & Infection